TIME BUDGET PRESSURE EFFECT, AUDITOR ETHICS, AUDIT FEE AND AUDITOR'S WORKING EXPERIENCES ON AUDIT QUALITY - Munidewi, Ida Ayu Budhananda; Sunarsih, Ni Made (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
Audit quality is the probability of an auditor finding and reporting an error or fraud that occurs in a client's accounting system. Audit quality is very important in ensuring that the accounting profession can fulfill its responsibilities to the public in producing reliable and quality audit reports. This study aims to test and obtain empirical evidence, audit ethics, audit fees, and work experience of auditors on audit quality at public accounting firms in Bali. The population in this study were 117 auditors at the Public Accounting Firm in Bali which were listed in the IAPI Directory in 2020, with a total sample of 67 respondents from 16 Public Accounting Firms obtained based on the non-probability sampling method with purposive sampling technique, namely the sampling technique. with certain considerations. The data analysis technique used is multiple linear regression analysis. The results showed that time budget pressure and auditor ethics had an effect on audit quality, while audit fees and auditor work experience had no effect on audit quality. Further research can develop this research by using other variables that have a theory of influence on audit quality. Keywords: Audit quality, time budget pressure, audit ethics, audit fees, auditor working experiences.